Характеристичне рівняння математичної моделі флаттера податливої до трансверсального зсуву пластини-смуги та алгоритм його розв’язання - Bodnar, V. O.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів; Marchuk, M. V.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів; Національний університет «Львівська політехніка», Львів; Pakosh, V. S.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів; Національний університет «Львівська політехніка», Львів (Pidstryhach Institute for Applied Problems of Mechanics and Mathematics of NAS of Ukraine, 2024)
Based on a variant of the refined plate theory, which allows for accurate consideration of boundary conditions in the forces on the face surfaces, a mathematical model of the behavior of a plate-strip subject to transverse shear under the action of an aerodynamic flow was obtained. The corresponding characteristic equation was constructed, which, unlike the case of using the classical plate theory, is a complete fourth-order polynomial. An algorithm for finding its roots was proposed and implemented in software. The use of the algorithm for specific values of the physical, mechanical and geometric parameters of the plate-strip under free hinged support was demonstrated. Cite as: V. O. Bodnar, M. V. Marchuk, V. S. Pakosh, “Characteristic equation of the mathematical model of the flutter of a plate-strip pliable to transversal shear and its solution algorithm,” Prykl. Probl. Mekh. Mat., Issue 22, 69–74 (2024) (in Ukrainian), https://doi.org/10.15407/apmm2024.22.69-74